Water scarcity and COVID-19 mortality in rural chilean areas - Ana Isabel Huaico-Malhue; Claudia Patricia Santibañez-Orellana; Edilia del Carmen Jaque-Castillo; Carolina Ojeda-Leal (Urbano)
The COVID-19 pandemic, caused by the spread of the SARS-CoV-2 virus around the world in March 2020, severely affected many areas of people’s life and health. Among the main ways to prevent its spread is by washing hands and food with soap and water. However, the latter is scarce in several municipalities of Chile, highlighting the difficulties of water supply at a national level. This work investigates the relationship between municipalities decreed by the government as being in a situation of water scarcity and the COVID-19 mortality levels found in rural areas between March 2020 and June 2021. Statistical data were used from different databases to correlate mortality rates with the level of municipal development and access to a drinking water network. A negative correlation was obtained between high COVID-19 mortality and low levels of communal development and connection to the drinking water network. As a result, it is deemed necessary to take into account geographical variables, such as water scarcity, in the generation of public health policies and water resource management.